2019
DOI: 10.1111/grow.12293
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of government‐supported provincial innovation competitiveness—Evidence from China

Abstract: Government support plays a crucial role in enhancing regional innovation capabilities and creating distinctive innovation clusters. Using the innovation competitiveness indicators of the 31 provinces in China, this paper examines the provincial government collaboration and innovation competitiveness values through Super‐SBM data envelopment analysis and analytic hierarchy process. Then, the particle swarm optimization (PSO) algorithm is employed to relate government collaboration to innovation competition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
1
13
0
1
Order By: Relevance
“…The results also showed that government subsidy promoted the R&D decisions and the R&D intensity of construction firms, although the effect was relatively small. The previous studies have also stressed the role of complementary or substitute influence of government subsidies on firms' R&D investments (Wallsten, 1999;Czarnitzki and Delanote, 2017;Wang et al, 2019). The results of this study confirmed that government subsidy has a complementary effect on the R&D intensity of construction firms.…”
Section: Technological Innovation In Constructionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results also showed that government subsidy promoted the R&D decisions and the R&D intensity of construction firms, although the effect was relatively small. The previous studies have also stressed the role of complementary or substitute influence of government subsidies on firms' R&D investments (Wallsten, 1999;Czarnitzki and Delanote, 2017;Wang et al, 2019). The results of this study confirmed that government subsidy has a complementary effect on the R&D intensity of construction firms.…”
Section: Technological Innovation In Constructionsupporting
confidence: 80%
“…In addition, government support plays an important role in firms' technological innovation (Wang, 2014); such support mainly consists of government subsidies, tax policies and intellectual property protection. Currently, government subsidies are considered as being the main fiscal policies to stimulate innovation (Wang et al, 2019). Therefore, government subsidy is included in the equations.…”
Section: Technological Innovation In Constructionmentioning
confidence: 99%
“…If the state stops funding for 2 VOLUME XX, 2017 scientific research, the consequences are unthinkable, and private investment cannot make up for the gap left by state funding [6]. Mazzucato [7], Zhang [8] and Wang [9] explained the reasons for government access to the field of innovation from the perspectives of risk, publicity, spillover and information asymmetry of innovation. Second, explore the effect of government support on innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for the purpose of validation and to give robustness to the results, seven studies compare different DEA models in the fields of education (Glass et al., 2006; Waldo, 2007), health (Halkos and Tzeremes, 2011a; Seth and Patel, 2014), environment (Halkos and Tzeremes, 2010a), local government (Halkos and Tzeremes, 2010b), and innovation (Halkos and Tzeremes, 2013) and three implement both DEA and non‐DEA approaches in the fields of local government (Zabala‐Iturriagagoitia et al., 2007; Wang et al., 2019) and education (Tochkov et al., 2012). The combination of several techniques is especially common when the application fields are heterogeneous and interdisciplinary, as these characteristics hamper the establishment of wide accepted models.…”
Section: Method‐wise Focus Of the Literaturementioning
confidence: 99%
“…From the perspective of the level of analysis, a consistent portion of these studies involves the evaluation of regional policies (Shi and Yang, 2008; Halkos and Tzeremes, 2010b, 2011b; Vieira et al., 2018; Natesan and Marathe, 2017; Titl and De Witte, 2021), with a special attention given to the study case of Spain (Zabala‐Iturriagagoitia et al., 2007; López et al., 2008), while the majority of the other studies focuses on the municipal and provincial levels (Broersma et al., 2013; Asatryan and De Witte, 2015; Cordero et al., 2017; Wang et al., 2019; Ma et al., 2020).…”
Section: Application‐wise Focus Of the Literaturementioning
confidence: 99%